TRANSPORT AS A FACTOR ENSURING REGIONAL COMPETITIVENESS (Web of Technology: Multidimensional Research Journal, 2026)
This article analyzes the role of the transport system in the modern economy, its key functions, and its significance in regional development. Particular attention is given to the economic integration, social connectivity, standardization, environmental sustainability, and innovative functions of transport, while substantiating their influence on the national economy and the quality of transport services. Furthermore, the study examines the priority directions for the development of Uzbekistan’s transport system, including the insufficient level of transport infrastructure development, the low quality of transport services, regional disparities in transport accessibility, the slow pace of digitalization processes, and the challenges associated with the implementation of transport projects. The article also highlights the importance of comprehensive approaches to addressing these issues, emphasizing the introduction of innovative technologies and the role of strategic planning in enhancing the efficiency and competitiveness of the transport sector.